GAMBARAN KEJADIAN MENGGIGIL PADA PASIEN PASKA OPERASI GENERAL ANESTESI DI RUMAH SAKIT - Arfi, Erfinawati (Media Husada Journal Of Nursing Science, 2024)
Postoperative shivering is muscle activity during the initial recovery after anesthesia. Patients whose body functions are affected by anesthesia will be depressed resulting in a decrease in metabolism and a decrease in body temperature. When patients begin to regain consciousness, they complain of feeling cold and uncomfortable. The aim of this study was to determine the description of the incidence of shivering in patients after general anesthesia surgery at HAMBA Muara Bulian Hospital, Batanghari Regency. This research used a descriptive quantitative research design, the population and research sample were all 643 patients who underwent surgery at HAMBA Regional Hospital. Sampling in this study used accidental sampling with a sample size of 87 respondents, and data analysis used univariate analysis. The instrument used in this research used an observation sheet. The research results showed that 86.2% of respondents experienced post-operative shivering, 56.3% of respondents had an operation time of > 2 hours, 72.4% of respondents received parenteral anesthesia. and 46.0% of respondents with general anesthesia surgery with grade 3 shivering were 40 respondents (46.0%). Most respondents experienced shivering during long operations using parenteral anesthesia and the degree of shivering felt throughout the body. Hospitals should be able to create procedures/SOPs for the use of body warming blankets to reduce shivering after surgery for respondents in addition to using pharmacological therapy.